Handicraft programs and library transformation for social inclusion to develop Generation Z's hard skills - Rum, Muhammad; Syamsuddin, Syamsuddin; Harun, Makmur (Universitas Padjadjaran, 2026)
Background: This study examines library transformation through social inclusion, focusing on skills development programs for Generation Z implemented by Omah Sinau and Ilham community libraries in Jambi City. There is a need for more information on how community libraries that are already based on social inclusion develop the knowledge and skills of Gen Z. Purpose: The study aimed to understand how Omah Sinau and Ilham community libraries have transformed into innovative and inclusive spaces and become hubs for creative, social, and digital activities for Gen Z. Methods: This study employed a qualitative research design. Informants were selected through purposive sampling, including government officials, community library managers, and Gen Z members. Results: Findings revealed that Gen Z female members were the dominant group, accounting for approximately 62%, and were primarily students. Findings also found that the skills development program involving handicrafts among Gen Z was implemented through exploration, socialization, and action phases. Findings also demonstrated that the handicraft products produced included bags, decorative flowers, piggy banks, decorative lamps, children’s toys, souvenirs, hand soap, beads, food-grade items, and decorative flower stems. Conclusion: The Gen Z skills development program developed by Omah Sinau and Ilham community libraries is not merely about meeting their needs, but also a strategic step towards transforming libraries into relevant, innovative, and inclusive spaces. Implication: This study replicates the economic and skills empowerment of Gen Z, the transformation of spaces and facilities, and multi-stakeholder collaboration. It has implications for a paradigm shift in the functions of public libraries and motor learning methods (such as handicrafts) of Gen Z.